FACTORS RELATED TO EXCLUSIVE BREASTFEEDING IN INFANTS OF 6-24 MONTHS (Analytical Observational Study in 2 Work Area of Health Center in Hulu Sungai Utara Regency) - Sri Mufida Adhayati (Lambung Mangkurat University, 2021)
Exclusive Breast Milk (ASI) is breastfeeding without other additional food for infants. 0-6 months of age, because the best nutrition for babies is only obtained through breast milk. Based on data from the Hulu Sungai Utara District Health Office in 2018 the percentage of exclusive breastfeeding for infants 0-6 months is still 72.74%, it is known that the Sungai Turak Puskesmas work area has the lowest exclusive breastfeeding coverage, which is 6.59% followed by the Puskesmas Saturday market amounting to 49.74%. The purpose of this study was to analyze the relationship between maternal health conditions, place of delivery, support from health workers, support from husbands and promotion of formula milk with exclusive breastfeeding. The research design was analytic observational withmethod case control and the number of research samples was 60 respondents. The research instrument was a questionnaire sheet. Univariate data analysis describes the frequency distribution of each variable and bivariate data analysis using thetest chi-square with a significance level (α) of 5% (95% confidence level). The results showed that there was a relationship between maternal health conditions (p-value= 0.009), husband's support (p-value= 0.011), promotion of formula milk (p-value= 0.001) and exclusive breastfeeding. Meanwhile, there was no relationship between the place of birth and the support of health workers with exclusive breastfeeding, p> 0.05. The conclusion of this study is that there is a relationship between maternal health conditions, husband's support and promotion of formula milk with exclusive breastfeeding. There is no relationship between the place of birth and the support of health workers with exclusive breastfeeding.